Sign Detection Vision Based Mobile Robot Platform - Hairol Nizam Mohd Shah; Mohd Zamzuri Ab Rashid; Zalina Kamis; Mohd Shahrieel Mohd Aras; Nursabillilah Mohd Ali; Faizil Wasbari; Tengku Muhammad Mahfuz Tengku Anuar (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Vision system applied in electrical power generated mobile robot to provide a comfortable ride while providing comfort to tourist to interact with visitors. The camera is placed in front of the mobile robot to snap the images along in pathways. The system can recognized the sign which are right, left and up by using Harris corner algorithms and will be display in Graphical User Interface (GUI). A sign can be determined from the vertex coordinates according to the degree to distinguish the direction of the sign. The system will be tested in term of percentage of success in Harris point detection and availability to detect sign with different range. The result show the even though not all Harris point in an image can be detected but most of the images possible to recognise it sign direction.